The Image of Destination Austria as perceived by British Tourists - Buschhaus, Hilke Laurin (2016)
Over the past decades, tourism destination image (TDI) has been one of the most widely studied areas of tourism research. However, only few authors have researched the image of destination Austria thus far. This study applies the concept of TDI to the context of Austria as tourist destination region (Leiper, 1995) and the country’s perceived image by British consumers. Apart from measuring cognitive and affective images, behavioural intentions of British consumers will be tested. The study attempts to identify potential marketing gaps, leading to the relatively low British visitor numbers over the last years (Office for National Statistics, 2015). Basing on the empirical findings of this study, marketing recommendations will be given, based on the 4P marketing mix approach (Jobber & Chadwick, 2013). This paper takes a mixed method approach to the measurement of the perceived Austrian TDI. This is in line with suggestions by Echtner & Ritchie (1993) and responds to a common criticism that purely quantitative methods cannot grasp the entirety of TDI (e.g. Pikkemaat, 2004), as TDI formation does not only include tangible, but also intangible/psychological factors, for which a purely structured measurement is unlikely to account (Chen & Tsai, 2007) The study finds that British consumers have a rather positive image of Austria. Nevertheless distinct weaknesses of the image could be identified which are likely to be caused by marketing gaps (Gursoy, 2011). The Recommendations of this study provide actionable suggestions for improving the marketing strategy in order to attract more British consumers to Austria, as the data in this study revealed evident potential within the British market.